THE SHADOW OF STUNTING THREATS TO DEVELOPMENT: Highlights Of Intervention And Prevention From A Human Rights - Khoerunisa, Nisa; Annashr, Nissa Noor; Yogaswara, Dadan; Agustira, Delia; Ramdani, Sahrul (Department of Government, FISIP, Universitas Padjadjaran, 2024)
Human rights are increasingly being used in the health sector, particularly in the context of stunting, a prevalent issue in Tasikmalaya City, an area in the eastern Priangan region. The threat of stunting not only impacts physical health but also future human resources quality. This research aims to analyze the role of the Tasikmalaya City government in protecting human rights in the health sector, particularly in handling and preventing stunting. The research uses a qualitative approach with a descriptive analysis method to evaluate existing programs' availability, assessment, acceptability, and quality. The results show that stunting not only hinders individual children's growth but also has a long-lasting impact on development. The Tasikmalaya City government has made efforts to address stunting, but the implementation of these programs is still not optimal. Complex problems such as budgeting, socialization of stunting knowledge, and collaborative cooperation between cross-sectors require more comprehensive efforts.gb777